2016
DOI: 10.21500/19002386.2291
|View full text |Cite
|
Sign up to set email alerts
|

Esperanza en adolescentes y jóvenes peruanos: diferencias según el sexo y la edad

Abstract: El estudio describe las características diferenciales de la esperanza en jóvenes y adultos universitarios según el sexo y la edad a partir de las puntuaciones del Herth Hope Index, en su adaptación peruana (Castilla et al., 2014). Para ello se contó con la participación de 420 personas, varones (47.9 %) y mujeres (52.1 %), con edades entre 16 y 38 años (Media = 20.16; D.E.= 4.57). Los resultados muestran que las mujeres, en comparación con los hombres, son más propensas a experimentar cierto grado de esperanza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
0
0
2
Order By: Relevance
“…This opens a space for future studies, including considerations for postpandemic psychosocial intervention. Other studies referring to these variables, such as one carried out in 420 Peruvian university students, showed that women and older people were more likely to experience hope [64]. In addition, there is a report on 51 Mexican university students that also identified a higher level of resilience in males [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This opens a space for future studies, including considerations for postpandemic psychosocial intervention. Other studies referring to these variables, such as one carried out in 420 Peruvian university students, showed that women and older people were more likely to experience hope [64]. In addition, there is a report on 51 Mexican university students that also identified a higher level of resilience in males [51].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of hope have been found to reduce the suffering of cancer patients [63], including reducing the fear of death [57]. There is also evidence that women are more likely to experience a certain degree of hope compared with men [64]. Hope leads to the development of preventive behaviors that decrease the risk of disease [65].…”
Section: Introductionmentioning
confidence: 99%
“…En ese sentido, un estudio previo en Perú reportó que las mujeres y las personas de mayor edad dentro de un rango de 16 y 38 años obtuvieron puntuaciones más altas en esperanza (Caycho et al, 2016), corroborando los resultados de otras investigaciones con muestras angloparlantes (Marques et al, 2013;Snyder, 2000). No obstante, en México se reportó que las mujeres obtuvieron puntuaciones más elevadas en desesperanza con respecto a los varones (Valdez et al, 2014).…”
Section: Discussionunclassified
“…Sin embargo, estos resultados podrían extenderse a otras regiones urbanas del país que comparten ciertos patrones culturales. Por otro lado, sería pertinente analizar la invarianza factorial de HHI abreviado en función del sexo, tomando en cuenta las contradicciones entre nuestros resultados con muestra de Arequipa y los obtenidos en Lima (Caycho et al, 2016).…”
Section: Discussionunclassified